HIDROGEL EKSTRAK BONGGOL PISANG, RUMPUT LAUT DAN DAUN SIRIH UNTUK LUKA BAKAR - Eko Julianto; Sudiarto Sudiarto (MNJ (Mahakam Nursing Journal), 2018)
Wounds are daamage to the skin which causes a break in the continuity of skin tissue. One type of wound is burn. Burns are damage to the skin layer due to exposure to heat agents and chemicals. Damage to the skin layer can damage all layers of the skin from the epidermis, dermis and subcutaneous layers. Damage due to burns is also affected by the areaof the body exposed. The worst risk of burns is the damage and death of blood vessels and skin nerves which will lead to amputation. The latest techniques for treating burns are using a variety of synthetic dressings such a calcium alginate, hydrocolloid, foam, hydrogels and transparent film. One substitute for synthetic dressings is the use of hydrogels made from natural ingredients. Natural ingredients that are often used empirically as a treatment for burns are banana stens (Musa Paradisiaca), seaweed (Sargassum) and betel leaves (Piper batle). The three natural ingredients are then made into hydrogels to meet the moisture standard dressing. Specimens were tested in grade II burns in white rate (Rattus novergitus). Grade II burns are made bybiopsy method. The application of hydrogel as a dressing was carried out for 21 days, with identification and dressing changes performed every 2 days to see the effect on healing burns. This study used True Experiment method with Pre post group design. The result showed that the significance score of wound healing scores on the day 7th and 21st are 0,036 and 0,046 (<0,05 then Hais accepted). While the total significanse of thenumber of macrophages and fibroblasts on the 14th and 21st days was <0,05, so Ha wasaccepted. The significance value of the average number of bacteria on the 21st day was 0,017 (<0,05 then Ha was accepted).